Effects of Culture Conditions on Production of trans-Cinnamic Acid from Alkylbenzenes by Soil Microorganisms - Douros, John D. (1968)
The production of trans-cinnamic acid from various alkylbenzenes by soil microorganisms was studied intensively by use of a co-oxidation technique. The microorganisms were grown on n-paraffins, and they did not use aromatic compounds as a carbon source when the preferred substrate was present in the medium. The effects of cell population, co-oxidation time, and type and mode of addition of the alkylbenzenes on the yield of trans-cinnamic acid were investigated. Yields (5 g/liter) of a product consisting of trans-cinnamic acid (88 to 100%) and 5-phenylvaleric acid (0 to 12%) were obtained when the proper conditions were chosen. Of a variety of microorganisms studied, a soil isolate closely related to Cellulomonas galba was found to be best for the production of trans-cinnamic acid.